(untitled) (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Hirschsprung’s disease is a common cause of neonatal & infantile intestinal obstruction. The confirmed diagnosis of HD depends on histopathological demonstration of the complete absence of ganglion cells with the presence of hypertrophied nerve fibers in the distal bowel. So, rectal biopsy is the gold standard for diagnosis of HD no dought. Objectives: This study is an attempt to see the comparision between punch and fullthickness rectal biopsy to find out a low cost, easily performed technique with accurate histopathological results for diagnosis of HD, specially for poor and developing countries of the world. Methods: This was a cross sectional comparative study. Total 50 patients of suspected Hirschsprung’s disease were included in this study after fulfillment of inclusion criteria from November 2010 to March 2012 at Dhaka Shishu (Children) Hospital, Dhaka, Bangladesh. Results: Out of 25 cases, 17 were diagnosed as having HD in punch biopsy but in case of full-thickness rectal biopsy out of 25 cases 20 were diagnosed as having HD. The sensitivity was 80% and positive predictive value was 94.11% of punch rectal biopsy in relation to full-thickness rectal biopsy. Operation time was less in punch rectal biopsy (14 minutes) than full-thickness rectal biopsy (20.5 minutes). Cost was less in punch rectal biopsy (1850 taka) than full-thickness rectal biopsy (3500 taka). Post procedure hemorrhage occurred 1 case in punch rectal biopsy, whereas 2 cases occurred in full-thickness rectal biopsy. No perforation occurred in case of punch biopsy but 1 case developed perforation in full-thickness rectal biopsy. Conclusion: Punch rectal biopsy for diagnosis of HD is advantageous over fullthickness rectal biopsy in the form of less time, less cost, less complication but diagnostic efficacy is almost similar. DS (Child) H J 2019; 35(1) : 42-47